Seeking for the ideal stent graft - Isa C. T. Santos (2010)
Aortic aneurysms are localized dilatations of the aorta that if not treated may lead to death. One of the current treatments is endovascular repair, a minimal invasive procedure in which a stent graft is placed transluminally to prevent wall rupture shielding the aneurysm from blood pressure. Stent grafts are classified as class III medical devices. They are composed of a metallic scaffold covered by a polymeric membrane. While early devices were custom designed by the operating surgeon, nowadays several commercially devices are available. The introduction of new devices helped solving several complications, however other problems, like fatigue, still persist. Furthermore, innovative functions, namely measurement of the intrasac pressure, are demanded to improve patient's quality of life. Based on an acutely literature review, this article classifies stent grafts according to different characteristics and points out the guidelines for an ideal stent graft. Finally, it proposes new features to be included in the next generation of stent grafts.